Association between Health Literacy and Quality of Life among Elderly in the Upper Northeast of Thailand - Prachaiboon, Tiwakron; Banchonhattakit, Pannee; Sirisuwan, Petcherut; Namuang, Atchara; Heebkaew Padchasuwan, Natnapa; Sukrueangkul, Alongkorn (Health Science Journal of Thailand, 2022)
This is a cross-sectional analytical study that aims to study the association between health literacy and quality of life among elderly. In this study, the multistage stratified systematic random sampling was used to recruit 516 elderly samples. The data were collected by health literacy questionnaire and the World Health Organization Quality of Life questionnaire (WHOQOL-BREF) and multiple logistic regression was used for data analysis. The result revealed that factors associated with quality of life among elderly in the Upper Northeast of Thailand were adequate and excellent health literacy level (Adj. OR = 2.13; 95%CI: 1.38 - 3.28), monthly household income at 5,000-10,000 Baht (Adj. OR = 2.02; 95%CI: 1.25 - 3.27), and household income more than 10,000 Baht (Adj. OR = 4.87; 95%CI: 2.53 - 9.36), the occupation of agriculture (Adj. OR = 2.66; 95%CI: 1.68 - 4.19), the occupation of business, self-employed, government pensioner, and state enterprise (Adj. OR = 4.52; 95%CI: 1.92 - 10.63), living in municipal housing (Adj. OR = 2.09; 95%CI: 1.36 - 3.20), non-drinking alcohol (Adj. OR = 7.16; 95%CI: 4.18 - 12.28), and non-disability (Adj. OR = 2.24; 95%CI: 1.03 - 4.89). It can be concluded that the elderly had adequate and excellent levels of health literacy that were positively associated with good quality of life among the elderly. Therefore, factors such as household income, stable occupations, habitation, and drinking alcohol are important to improve the quality of life in the elderly.